2017
DOI: 10.1021/acs.analchem.6b04737
|View full text |Cite
|
Sign up to set email alerts
|

Open Port Probe Sampling Interface for the Direct Coupling of Biocompatible Solid-Phase Microextraction to Atmospheric Pressure Ionization Mass Spectrometry

Abstract: In recent years, the direct coupling of solid phase microextraction (SPME) and mass spectrometry (MS) has shown its great potential to improve limits of quantitation, accelerate analysis throughput, and diminish potential matrix effects when compared to direct injection to MS. In this study, we introduce the open port probe (OPP) as a robust interface to couple biocompatible SPME (Bio-SPME) fibers to MS systems for direct electrospray ionization. The presented design consisted of minimal alterations to the fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 45 publications
(136 reference statements)
0
105
0
Order By: Relevance
“…Electrospray ionization occurs readily from the porous material of the swab tip, similarly to paper spray 15, 16 and biocompatible solid phase micro-extraction fibers. 17, 18 …”
Section: Introductionmentioning
confidence: 99%
“…Electrospray ionization occurs readily from the porous material of the swab tip, similarly to paper spray 15, 16 and biocompatible solid phase micro-extraction fibers. 17, 18 …”
Section: Introductionmentioning
confidence: 99%
“…Gómez-Ríos et al reported the analysis of drugs of abuse in human urine and plasma at the sub-ppb concentration level by using an open port probe (OPP) ionization source. 30 Tascon et al quantified immunosuppressants in whole blood at the sub-ppb level with a microfluidic open interface (MOI) ionization source. 31 Coated blade spray 32 (CBS) was also used for the quantification od drugs of abuse in human urine and plasma.…”
Section: Resultsmentioning
confidence: 99%
“…As happens with the classic SPE cartridges, the SPME LC fiber is designed for single use; however, it can be reused by implementing a cleaning step after the desorption cycle with a mixture of solvents such as methanol, isopropanol and acetonitrile (Gomez‐Rios et al, ). The reusability of the fiber highly depends on factors such as sample matrix, the effectiveness of fiber cleaning and desorption conditions.…”
Section: Classification Of Microextraction Methodsmentioning
confidence: 99%
“…This method can detect prohibited substances in biofluids rapidly via direct analysis. The open port probe sampling interface was designed for direct coupling of biocompatible SPME fibers to MS systems for direct electrospray ionization and quantitative determination of clenbuterol, fentanyl and buprenorphine in human urine (Gomez‐Rios et al, ). These techniques are still in the early development stage with prototypes available.…”
Section: Classification Of Microextraction Methodsmentioning
confidence: 99%